2013
DOI: 10.4161/rna.24285
|View full text |Cite
|
Sign up to set email alerts
|

Small RNAs derived from the 5′ end of tRNA can inhibit protein translation in human cells

Abstract: Recently, it has been shown that tRNA molecules can be processed into small RNAs that are derived from both the 5′ and 3′ termini. To date, the function of these tRNA fragments (tRFs) derived from the 5′ end of tRNA has not been investigated in depth. We present evidence that conserved residues in tRNA, present in all 5′ tRFs, can inhibit the process of protein translation without the need for complementary target sites in the mRNA. These results implicate 5′ tRFs in a new mechanism of gene regulation by small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
269
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(277 citation statements)
references
References 39 publications
8
269
0
Order By: Relevance
“…Even though 5′ tRNA halves also repress protein biosynthesis (see above), 52 the mechanisms clearly differ: (1) the proposed terminal oligo-G motif of 5′ tRNA halves is either absent in the investigated 5′ tRFs or not crucial for the inhibitory potential, (2) 5′ tRFs do not target mRNA, (3) whereas 5′ halves associate with translation initiation factors and the translational silencer protein YB-1, 5′ tRFs associate with ribosomal particles (30S ribosomal subunits and polysomes in H. volcanii; polysomes, and RNPs smaller than 40S subunits in human cells). 57,64 How exactly these 5′ tRFs perform their action on the ribosome, and how they are processed awaits experimental clarification.…”
Section: Trna-derived Fragmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though 5′ tRNA halves also repress protein biosynthesis (see above), 52 the mechanisms clearly differ: (1) the proposed terminal oligo-G motif of 5′ tRNA halves is either absent in the investigated 5′ tRFs or not crucial for the inhibitory potential, (2) 5′ tRFs do not target mRNA, (3) whereas 5′ halves associate with translation initiation factors and the translational silencer protein YB-1, 5′ tRFs associate with ribosomal particles (30S ribosomal subunits and polysomes in H. volcanii; polysomes, and RNPs smaller than 40S subunits in human cells). 57,64 How exactly these 5′ tRFs perform their action on the ribosome, and how they are processed awaits experimental clarification.…”
Section: Trna-derived Fragmentsmentioning
confidence: 99%
“…Hutvagner et al reported that 5′ tRFs were able to efficiently inhibit in vitro translation, which was independent of mRNA target sites. 64 By examining the inhibitory potential of other human 5 'tRFs, a universally conserved GG dinucleotide at the 3′ terminus has been proposed as crucial functional determinant. Nevertheless, such a "mini motif " does not appear to be sufficient, since one of the identified 5′ tRFs that contained the GG sequence failed to inhibit translation.…”
Section: Trna-derived Fragmentsmentioning
confidence: 99%
“…Sperm sncRNA has been reported to induce transcriptional changes in the early embryo when injected into zygotes (Chen et al 2016, Sharma et al 2016, but whether these are direct or indirect transcriptional effects is unknown. Available evidence indicates that tRFs, like miRNA, reside predominantly in the cytoplasm (Garcia-Silva et al 2012) where they can associate with polyribosomes and affect translation (Sobala & Hutvagner 2013, Kumar et al 2014. It may be that the transcriptional changes within embryos in response to sperm sncRNA are mediated by post-transcriptional mechanisms (Cropley et al 2016).…”
Section: Small Non-coding Rnamentioning
confidence: 99%
“…These reviews highlight the conflicting reports of the biogenesis of tRF5s and tRF-3s, with some original reports on these molecules implicating DICER1, but a recent paper showing DICER1 is dispensable for the generation of most tRF-5s and tRF-3s [17]. Several recent papers have also shown that tRF-5s or tRF-3s can associate with Argonautes or participate in RNA silencing [18][19][20], while another paper argues tRF-5s cannot silence a reporter gene but rather function similarly to 5' tRNA halves and inhibit translation [21]. Despite this growing literature on tRFs there are still concerns that tRFs could simply represent degradation products of their extremely abundant parental molecules, or concerns that the reads seen in deep sequencing are biologically relevant since it is known tRNA modifications can affect reverse transcriptase [22].…”
Section: Introductionmentioning
confidence: 99%